Chaos in a Non-Autonomous Inductorless Active-RC Circuit - Muhammad Taher Abuelma'atti; Mazen M. Johar (Active and Passive Electronic Components)
Chaotic performance of a simple inductorless active-RC non-autonomous electronic circuit is reported. The circuit uses two operational amplifiers, an operational transconductance amplifier, a diode, two resistors, and one capacitor only. No discrete inductors are involved.